Pengaruh Lingkungan Kerja, Motivasi, dan Komunikasi Terhadap Kepuasan Kerja Pegawai Perusahaan Daerah Air Minum (PDAM) pada Divisi Hubungan Pelanggan Kota Balikpapan - Listya Dwi Nur Azizah; Misna Ariani; Imam Arrywibowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study was to determine the influence of Work Environment, Motivation, and Communication on Job Satisfaction of Employees at the Regional Drinking Water Company (PDAM) in the Customer Relations Division of Balikpapan City. The research used quantitative research. The sampling technique used purposive sampling with a sample size of 75 employees at the Regional Drinking Water Company. Data collection was conducted by distributing questionnaires. This study used Smart-PLS to process the data. Data analysis methods used outer models, inner models, basic equations, and bootstrapping tests. The results showed that the variables of Work Environment, Motivation, and Communication influenced Job Satisfaction of Employees at the Regional Drinking Water Company (PDAM) in Balikpapan City.